Management of Feline Corneal Sequestrum with Use of Third Eyelid Flap after Partial Keratectomy - Demir, Aynur (Acta Scientiae Veterinariae, 2024)
Background: Deep corneal sequestrum is a lesion that occurs in the middle layers of the cornea and typically leads to significant discomfort. This condition is a common and significant ophthalmologic issue in cats, which can significantly affect the cat’s quality of life; if left untreated, it can lead to permanent vision loss. These findings underscore the importance of prompt and effective management strategies for deep corneal sequestrum in cats, with the third eyelid flap (TEF) application following partial keratectomy emerging as a potential treatment approach warranting further investigation. The study’s objective was to evaluate the efficacy of the TEF application following partial keratectomy in managing deep corneal sequestrum in 50 cats (65 eyes) suffering from deep corneal sequestrum. Materials, Methods & Results: Medical records, including the signalment, medical history, treatment procedures, and ocular status of 50 cats diagnosed with corneal sequestrum and treated with partial keratectomy followed by TEF, were retrospectively evaluated. The breed-wise distribution involved 26 Persians, 11 British Shorthairs, 6 Scottish Folds, 6 Domestic Shorthairs, and 1 Sphynx. Thirty-five cats were unilaterally, and 15 were bilaterally affected. The average age was 3.47 years (ranging between 5 months and 12 years). The average period for TEF application was 27.29 days (range =10-35 days), and the follow-up period varied from 2 to 50 months (Average = 14.1 months). The final follow-up revealed no change in 8 of 19 eyes regarding postoperative pale stromal pigment effusion, which disappeared in 9 and darkened in a 2 case. After complete resection in 3 eyes of 3 cases and incomplete resection in 2 eyes of 2 cases, recurrence rates were 6.52% and 10.52%, respectively, and corneal sequestrum was successfully treated with a 2nd surgical intervention in 3 eyes. 93.47% of patients (43 eyes) of 46 eyes whose feline corneal sequestrum (FCS) were totally removed by lamellar keratectomy were successfully treated with TEF. Discussion: In conclusion, 93.47% of patients (43 eyes) of 46 eyes whose feline corneal sequestrum (FCS) were totally removed by lamellar keratectomy were successfully treated with TEF. The results of this study demonstrate the effectiveness of TEF application in managing deep corneal sequestrum in cats. The high success rate and low recurrence rates support TEF as a reliable treatment option following partial keratectomy for deep corneal sequestrum cases. TEF was an effective treatment with highly satisfactory visual and cosmetic outcomes for deep and full-thickness feline corneal sequestrum. The TEF technique applied after partial keratectomy for the treatment of FCS can be considered an advantageous and practical method due to reasons such as providing rapid healing, being simpler, faster, and easier to apply compared to other aggressive interventional treatments, cost-effectiveness, not requiring specific tools and equipment or graft material, and showing no tissue rejection. However, careless application may pose certain risks; therefore, it is recommended under the guidance of a specialist. Similar to several other techniques, TEF application resulted in minimal corneal scarring along the visual axis. However, careless application may pose certain risks; therefore, it is recommended under the guidance of a specialist. Similarly, TEF application resulted in minimal corneal scarring along the visual axis, but recurrence may occur in some cases, necessitating a second surgical intervention. These findings provide significant contributions to clinical practice for the effective management of ophthalmic issues in cats. Keywords: corneal sequestrum, feline, ophthalmology, partial keratectomy, third eyelid flap.